A COMMUNICATION RISK FRAMEWORK FOR REQUIREMENTS CHANGE IN GLOBAL SOFTWARE DEVELOPMENT - KHAN, ARIF ALI (2013)
Global Software Development (GSD) has gained great attention during the past decade or so; and it is also being implemented throughout the world. Due to the economic and strategic effects of GSD, it is treated as a substitute to a single site. The geographically dispersed environment makes software development a complicated task and brings out several challenges such as geographical, socio-cultural and temporal distances. The process of Requirements Change Management (RCM) in the GSD is thought to be puzzling even in the finest situations. Due to effect of geographical, socio-cultural and temporal distances, various communication risks arise among the distributed team members during the process of RCM.